A traveling wave suppression impedance gradient prepreg, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611476060.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-30
AI Technical Summary
塑料薄膜为致密连续膜,覆盖在复合材料表面时阻碍气体排出,在与复合材料二次固化或胶接固化过程中容易在界面处形成弥散性孔隙缺陷,影响复合材料的内部质量和力学性能
(1)本发明将传统塑料薄膜载体的电阻膜变革为织物形式的预浸料,预浸树脂与结构预浸料的树脂体系相容,可与复合材料整体共固化成型。功能层与结构层之间形成树脂基体连续相,而非依赖胶层粘接。本发明以织物为载体、导电层分布于织物纤维表面、导电纳米材料相互搭接,从而形成的织物-导电层结构为具有贯通孔隙的多孔结构,预浸料铺贴后仍可透气和真空导气,共固化时不易在界面产生弥散性孔隙缺陷,保证了固化后复合材料的内部质量。导电织物在面内可剪切变形,能够随形铺贴于双曲率等复杂型面,铺贴工艺性与常规结构预浸料一致,不起皱、不架桥,解决了铺贴性问题。
Smart Images

Figure CN123004089A_ABST
Abstract
Description
Technical Field
[0001] This invention specifically relates to a traveling wave suppression impedance gradient prepreg, its preparation method, and its application, belonging to the field of electromagnetic wave absorption functional composite materials technology. Background Technology
[0002] In radar stealth technology, besides specular reflection scattering, surface traveling waves propagating along the surface of metal or composite structures are another significant source of scattering. When these traveling waves propagate to discontinuities such as structural edges, gaps, and tips, strong edge scattering occurs, forming a significant peak in the radar cross section (RCS), severely threatening the low detectability performance of equipment. Therefore, effectively suppressing surface traveling waves is one of the key technologies for radar scattering control.
[0003] Existing traveling wave suppression technologies mainly employ impedance gradient films (also known as resistive gradient films or R-cards). These involve fabricating a resistive layer on the surface of a plastic film such as polyethylene terephthalate (PET) or polyimide (PI) through methods like screen printing, spraying, or magnetron sputtering. The sheet resistance of this resistive layer gradually increases along the traveling wave propagation direction. The low-resistance end of the impedance gradient film is then bonded to a conductive substrate, utilizing the gradient impedance to absorb the traveling wave current without reflection. For example, a patent published by the University of Electronic Science and Technology of China (CN102570047B) discloses an edge-gradient impedance loading film that uses progressively periodic square aluminum foil patches and complementary progressively periodic aperture units on the impedance film to achieve edge scattering suppression. However, this traditional impedance gradient film has the following problems in engineering applications: (1) Poor adhesion performance. PET, PI and other plastic films have low surface energy and can only be bonded to structural materials by pressure-sensitive adhesives or adhesives. The interfacial bonding strength is low and they are prone to debonding, curling, and falling off under service environments such as vibration and temperature cycling. It is difficult to form a reliable long-term connection with load-bearing structures.
[0004] (2) Impermeable. Plastic film is a dense and continuous film. When it covers the surface of composite material, it hinders the gas from escaping. During the secondary curing or adhesive curing process with composite material, it is easy to form diffuse pore defects at the interface, which affects the internal quality and mechanical properties of composite material.
[0005] (3) No deformation capability. Plastic film is a continuous film that cannot be stretched in the plane. It cannot be laid in a shape to complex surfaces such as hyperbolic surfaces. It is easy to wrinkle and bridge during laying, which makes it difficult to meet the application requirements of complex curved edge structures such as the air intake lip and wing leading edge of aircraft.
[0006] (4) Electrically, the existing resistive film is mainly composed of distributed capacitance between conductive particles / conductive film. The traveling wave current is prone to resonance under capacitive load, causing scattering peaks. However, plastic film is an isotropic continuous medium and lacks structural means to adjust the distributed inductive reactance, thus limiting the degree of freedom in adjusting electrical performance.
[0007] On the other hand, the use of advanced composite materials in the aerospace field is increasing, and achieving structural-functional integration from the material design level is a development trend. If the traveling wave suppression functional layer can be provided in the form of prepreg, allowing it to be laid like conventional structural prepregs and co-cured with the structural prepreg, the aforementioned problems of adhesive strength, air permeability, and conformability can be fundamentally solved. Patent CN106671514B discloses a discontinuous impedance gradient structural wave-absorbing composite material, but it is a multi-layered laminated plate structure, not a layable co-cured prepreg form, and its impedance gradient direction is along the thickness direction, so it cannot suppress in-plane traveling waves. Patent CN112538761B discloses an integrated impedance gradient flexible wave-absorbing material, whose gradient direction is also along the thickness direction of the substrate. The substrate is sponge, non-woven fabric, or spacer fabric, and it is also not a traveling wave suppression prepreg intended for co-curing with structural components.
[0008] In summary, existing impedance gradient films suffer from poor adhesion, lack of air permeability, no deformation capability, and difficulty in co-curing with composite material structures. Furthermore, existing resistive films only possess distributed capacitive reactance, lack inductive reactance adjustment methods, and have limited traveling wave suppression electrical performance. Therefore, there is a need for an impedance gradient prepreg that can co-cur with composite material structures and possesses both traveling wave suppression electrical performance and lay-up process performance. Summary of the Invention
[0009] This invention addresses the shortcomings of existing technologies by providing a traveling wave suppression impedance gradient prepreg, its preparation method, and its applications. The traveling wave suppression impedance gradient prepreg provided by this invention is a prepreg with continuous fiber fabric as the carrier, conductive nanomaterials loaded on the surface of the fiber bundles as the conductive layer, and a thermosetting resin that can be co-cured with structural prepregs as the matrix. It can be co-cured with structural prepregs, exhibits reliable adhesion, good air permeability, high internal quality, deformability, good lay-up processability, excellent traveling wave suppression electrical properties, and precisely adjustable and controllable surface resistance after curing.
[0010] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: a traveling wave suppression impedance gradient prepreg, wherein the traveling wave suppression impedance gradient prepreg comprises a continuous fiber fabric, a conductive layer and a prepreg resin; The continuous fiber fabric includes warp fiber bundles extending along the warp direction and weft fiber bundles extending along the weft direction, wherein the warp fiber bundles and the weft fiber bundles interweave to form a fabric structure. The conductive layer is a conductive nanomaterial loaded on the surface of the warp fiber bundle and / or the weft fiber bundle, and the conductive nanomaterials overlap each other to form an electrically continuous conductive network along the in-plane direction of the continuous fiber fabric. The prepreg resin is impregnated in a continuous fiber fabric and a conductive layer to form a prepreg shape that can be laid out. The surface sheet resistance of the conductive layer is gradually distributed along a first direction within the continuous fiber fabric, and the first direction is the direction of conduction of the traveling wave current during use; the prepreg resin is a thermosetting resin that can be co-cured with the structural prepreg.
[0011] Furthermore, the surface sheet resistance ranges from 5Ω / sq to 20000Ω / sq.
[0012] Furthermore, the gradual distribution of the surface sheet resistance is selected from one or a combination of the following: a. The gradient distribution is arranged in sequence along the first direction, with multiple impedance segments having different surface sheet resistances of adjacent impedance segments, and the surface sheet resistance of each impedance segment changes monotonically along the first direction. b. The surface sheet resistance changes continuously and gradually along the first direction.
[0013] Furthermore, the gradient distribution includes a low-resistance section, a transition section, and a high-resistance section. The lowest end of the low-resistance section is used for electrical connection with the conductive substrate. The surface sheet resistance of the low-resistance section is 5Ω / sq to 150Ω / sq, the surface sheet resistance of the transition section is 150Ω / sq to 200Ω / sq, and the surface sheet resistance of the high-resistance section is 200Ω / sq to 20000Ω / sq.
[0014] Furthermore, the surface sheet resistance of the multiple impedance segments is distributed along the first direction according to at least one of the following: linear profile, exponential profile, cosine square profile, Taylor weighted profile, and Klopfenstein profile.
[0015] Furthermore, the number of the plurality of impedance segments is 2 to 20, and the width of each impedance segment along the first direction is 5 mm to 150 mm.
[0016] Furthermore, the continuous fiber fabric is a plain weave fabric, with its warp and weft densities each independently ranging from 10 to 30 strands / cm. The warp fiber bundles and the weft fiber bundles form overlapping nodes of the conductive network at their interlacing points. The conductive nanomaterials between adjacent overlapping nodes constitute a distributed capacitance along the first direction, and the conductive fiber bundle segments extending along the first direction constitute a distributed inductance. The distributed inductance and the distributed capacitance form an inductive-capacitive distributed parameter network along the first direction, which is used to adjust the transmission characteristics of the traveling wave current within the target frequency band.
[0017] Furthermore, the thickness of the conductive layer formed by the conductive nanomaterial in at least a portion of the low-resistivity section should be less than 10 μm, thereby achieving an efficient capacitance regulation mechanism. In the low-resistivity section, the volume conductivity of the conductive layer is not less than 6.7 S / cm, and in the transition section, the volume conductivity is not less than 5 S / cm.
[0018] Furthermore, the fibers of the continuous fiber fabric are one or more of the following: quartz fiber, glass fiber, high silica fiber, basalt fiber, and aramid fiber.
[0019] Further, the conductive nanomaterial is one or more of carbon nanotubes, graphene, graphite, carbon black, carbon nanofibers, and MXene (two-dimensional transition metal carbides, nitrides, or carbonitrides); preferably, the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5 nm to 50 nm and a length of 5 μm to 250 μm.
[0020] Furthermore, the thermosetting resin is one or more of the following: medium-temperature epoxy resin, high-temperature epoxy resin, bismaleimide resin, cyanate ester resin, polyimide resin, and phenolic resin.
[0021] Furthermore, the loading amount of the conductive nanomaterial on the continuous fiber fabric is 0.01 g / m² to 12 g / m²; preferably 0.5 g / m² to 10 g / m².
[0022] Furthermore, the areal density of the continuous fiber fabric is 30g / m² to 250g / m², and the thickness is 0.04mm to 0.25mm.
[0023] Furthermore, the preimpregnated resin has a mass fraction of 30% to 50% in the traveling wave suppression impedance gradient preimpregnated material.
[0024] Furthermore, the areal density of the traveling wave suppression impedance gradient prepreg is 60 g / m² to 250 g / m², the single-layer cured thickness is 0.04 mm to 0.25 mm, and the volatile content is not greater than 1.5%; preferably, the areal density is 150 g / m² to 200 g / m², the single-layer cured thickness is 0.08 mm to 0.15 mm, and the volatile content is not greater than 1.5%.
[0025] Furthermore, the continuous fiber fabric also includes multiple impedance gradient regions arranged along a second direction perpendicular to the first direction, with adjacent impedance gradient regions separated by insulating fiber zones that are not loaded with conductive nanomaterials; wherein, the surface sheet resistance distribution of the multiple impedance gradient regions is the same or different, so as to form a patterned impedance distribution within the same fabric surface.
[0026] This invention also provides a method for preparing a traveling wave suppression impedance gradient prepreg, the method comprising the following steps: S1. Prepare a conductive nanomaterial dispersion; the conductive nanomaterials are uniformly dispersed in the conductive nanomaterial dispersion. S2. The conductive nanomaterial dispersion is loaded onto a continuous fiber fabric by physical deposition, and by controlling the concentration of the conductive nanomaterial dispersion and / or the number of physical depositions and / or the partitioned deposition range, the surface sheet resistance of different areas of the continuous fiber fabric is distributed according to a preset distribution, forming a conductive fabric with a gradually changing surface sheet resistance along the first in-plane direction. S3. The thermosetting resin is made into a resin film, and the resin film is combined with conductive fabric by hot melt bonding to form a prepreg, thus obtaining a traveling wave suppression impedance gradient prepreg.
[0027] Furthermore, in step S1, the dispersant used to disperse the conductive nanomaterials is an aqueous dispersant, and the amount of dispersant used is no more than 100% of the mass of the conductive nanomaterials.
[0028] Preferably, between step S2 and step S3, a step of stabilizing the conductive fabric is further included; so that the change rate of the surface sheet resistance of the traveling wave suppression impedance gradient prepreg after co-curing is not greater than 30% compared with the surface sheet resistance before co-curing.
[0029] Preferably, in step S2, the surface sheet resistance of the conductive fabric is detected online using a four-probe method, and the concentration of the conductive nanomaterial dispersion and / or the number of physical depositions are adjusted according to the detection results.
[0030] The present invention also provides a composite material component integrating wave-absorbing structure and function, comprising a structural prepreg stack and at least one layer of traveling wave suppression impedance gradient prepreg provided by the present invention. The traveling wave suppression impedance gradient prepreg is laid on the surface or between the layers of the structural prepreg stack, wherein the lowest end of the surface sheet resistance of its low-resistance section is electrically connected to the conductive matrix, and the high-resistance section extends to the edge of the structure along the traveling wave propagation path. The traveling wave suppression impedance gradient prepreg and the structural prepreg stack are co-cured to form an integral structure.
[0031] This invention also provides an application of a traveling wave suppression impedance gradient prepreg for traveling wave suppression in the edge structure of composite materials in aircraft or spacecraft.
[0032] The beneficial effects of this invention are: (1) This invention transforms the resistive film of the traditional plastic film carrier into a prepreg in the form of a fabric. The prepreg resin is compatible with the resin system of the structural prepreg and can be co-cured with the composite material as a whole. A continuous resin matrix phase is formed between the functional layer and the structural layer, rather than relying on adhesive layer bonding. This invention uses fabric as a carrier, with conductive layers distributed on the surface of the fabric fibers and conductive nanomaterials overlapping each other. The resulting fabric-conductive layer structure is a porous structure with interconnected pores. After the prepreg is laid, it can still be breathable and vacuum-guided. During co-curing, it is not easy to generate diffuse pore defects at the interface, ensuring the internal quality of the composite material after curing. The conductive fabric can be sheared and deformed in the plane, and can be laid on complex surfaces such as hyperbolic surfaces. The laying process is consistent with that of conventional structural prepregs. It does not wrinkle or bridge, solving the laying problem.
[0033] (2) The impedance gradient prepreg of the present invention forms a continuous resin matrix phase between the prepreg and the structural layer. Through the joint control of the fabric structure and the conductive layer structure, the impedance gradient prepreg is well co-cured and bonded with the structural layer in both low-resistance and high-resistance regions, i.e. the whole, with an adhesion strength of more than 25MPa. This solves the problem that traditional resistive films can only rely on adhesive layers for bonding and are easy to detach and fall off. It also solves the problem that the conductive layer has a large impact in different regions, especially in low-resistance regions, and achieves the same lifespan as the structural composite material.
[0034] (3) The impedance gradient prepreg provided by the present invention involves the coexistence of multiple resistances over a very wide range and they are mutually conductive and continuous, thus achieving the three requirements of wide sheet resistance distribution, continuous sheet resistance distribution, and consistent thickness of the impedance gradient material.
[0035] (4) The warp and weft interwoven structure of the fabric enables the conductive fiber bundles along the traveling wave conduction direction to form a distributed inductance, which, together with the distributed capacitance between the conductive nanomaterials, forms an inductive-capacitive distributed parameter network. The inductive reactance can be adjusted using the warp and weft weaving structure to compensate for the traveling wave resonance caused by the simple capacitive conductive network, achieving non-reflective absorption of the traveling wave current in a wide frequency band. Experimental results show that the traveling wave suppression sample made using the impedance-gradient fabric of this invention can suppress the traveling wave peak of the metal plate by up to 36 dB in the range of 0.44 GHz to 9.41 GHz, and the traveling wave suppression coefficient can reach up to 61 dBsm·m. -1 It outperforms existing graded impedance films by 3~5 dBsm·m -1 above. Attached Figure Description
[0036] Figure 1 This is a schematic diagram of the cross-sectional structure of an impedance-gradient prepreg. Figure 2 A top view schematic diagram of a continuous fiber fabric for a traveling wave suppression impedance gradient prepreg. Figure 3 A schematic diagram of a surface with gradually varying sheet resistance profile; Figure 4 Equivalent circuit diagram of the distributed parameter network of fabric capacitance; Figure 5 A schematic diagram of a component co-cured with traveling wave suppression impedance gradient prepreg and structural prepreg; Figure 6 This is a comparison chart of the measured traveling wave suppression effect in Example 2.
[0037] Explanation of reference numerals in the attached figures: 1-Prepreg resin; 2-Continuous fiber fabric; 3-Conductive network; 4-Conductive matrix; 5-Structural prepreg laminate; 6-Traveling wave suppression impedance gradient prepreg; 7-Electrical connection area between low-resistance end and conductive matrix. Detailed Implementation
[0038] The specific embodiments of the present invention will be described in detail below. The present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used is for describing particular embodiments only and is not intended to limit the invention.
[0040] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this invention are all commercially available industrial products or chemical reagents.
[0041] To address the problems of existing impedance gradient film materials such as poor adhesion, lack of air permeability, lack of deformation ability, difficulty in co-curing with composite material structures, and the fact that existing resistive films only have distributed capacitive reactance, lack inductive reactance adjustment means, and have limited traveling wave suppression electrical performance.
[0042] This invention provides a traveling wave suppression impedance gradient prepreg, comprising a continuous fiber fabric, a conductive layer, and a prepreg resin. The continuous fiber fabric includes warp fiber bundles extending along the warp direction and weft fiber bundles extending along the weft direction, the warp and weft fiber bundles interwoven to form a fabric structure. The conductive layer is a conductive nanomaterial loaded on the surface of the warp and / or weft fiber bundles, the conductive nanomaterials overlapping to form an electrically continuous conductive network along the in-plane direction of the continuous fiber fabric. The prepreg resin is impregnated in the continuous fiber fabric and the conductive layer to form a prepreg shape that can be laid and molded. The surface sheet resistance of the conductive layer is gradually distributed along a first direction in-plane of the continuous fiber fabric, the first direction being the direction of travel wave current conduction during use. The prepreg resin is a thermosetting resin capable of co-curing with the structural prepreg. A cross-sectional structural schematic diagram of this impedance gradient prepreg is shown below. Figure 1 As shown.
[0043] The traveling wave suppression impedance gradient prepreg provided by this invention is a traveling wave suppression impedance gradient prepreg with continuous fiber fabric as the carrier, conductive nanomaterials loaded on the surface of the fiber bundles as the conductive layer, and a thermosetting resin that can be co-cured with the structural prepreg as the matrix. This invention transforms the resistive film of the traditional plastic film carrier into a prepreg in the form of a fabric, so that the impedance gradient functional layer itself is a prepreg that can be laid and molded. The prepreg resin is compatible with the resin system of the structural prepreg, so it can be co-cured and molded as a whole with the composite material, realizing the integration of traveling wave suppression function and structural load-bearing function.
[0044] This invention uses fabric as a carrier, with conductive layers distributed on the surface of the fabric fibers and conductive nanomaterials overlapping each other. The resulting fabric-conductive layer structure is a porous structure with interconnected pores. Even after the prepreg is laid, it remains breathable and allows for vacuum ventilation. During co-curing, it is less prone to diffuse porosity defects at the interface, ensuring the internal quality of the cured composite material. The conductive fabric can be sheared and deformed in-plane, allowing it to be laid conformally to complex surfaces such as hypercurvature. The laying process is consistent with conventional prepreg structures, without wrinkling or bridging, thus solving the layability problem.
[0045] The impedance-gradient prepreg of this invention forms a continuous resin matrix phase between itself and the structural layer. Furthermore, the conductive layer formed by this invention is distributed on the surface of the fabric fibers, resulting in a porous structure with interconnected pores. Specifically, by controlling the relative content of the dispersant and the amount of conductive material used when forming the conductive layer, the conductive fabric maintains a good bonding interface with the resin even in the low resistance range (5~150Ω / sq). Therefore, through the combined control of the fabric structure and the conductive layer structure, the impedance-gradient prepreg, regardless of whether it is in a low or high resistance region, exhibits excellent co-curing and bonding with the structural layer, achieving an adhesion strength of over 25MPa. This solves the problem of traditional resistive films relying solely on adhesive layers for bonding and prone to detachment, and addresses the issue of significant influence of the conductive layer in different regions, especially in low resistance regions, achieving the same lifespan as the structural composite material.
[0046] Specifically, the gradual distribution of the surface sheet resistance is selected from one or a combination of the following: a. The gradient distribution is arranged in sequence along the first direction, with multiple impedance segments having different surface sheet resistances of adjacent impedance segments, and the surface sheet resistance of each impedance segment changes monotonically along the first direction. b. The surface sheet resistance changes continuously and gradually along the first direction.
[0047] Specifically, the gradient distribution includes a low-resistance section, a transition section, and a high-resistance section. The lowest end of the low-resistance section is used for electrical connection with the conductive substrate. The surface sheet resistance of the low-resistance section is 5Ω / sq to 150Ω / sq, the surface sheet resistance of the transition section is 150Ω / sq to 200Ω / sq, and the surface sheet resistance of the high-resistance section is 200Ω / sq to 20000Ω / sq, thus enabling the material to obtain good traveling wave suppression performance.
[0048] This invention treats fabrics with a conductive nanomaterial dispersion containing a small amount of dispersant, enabling the conductive nanomaterials to overlap and resulting in a conductive network with higher conductivity (generally ≥10S / cm, up to 100S / cm) compared to coating systems and polymer dispersion systems. This allows for precise adjustment of the surface sheet resistance within the range of 5Ω / sq to 20000Ω / sq, while maintaining a relatively small conductive nanolayer thickness. This achieves: a) a consistent method for customizing patterned impedances across a wide range of resistances within the same fabric surface, ensuring good electrical continuity when gradient resistances coexist; b) a small thickness difference between high and low resistance regions, significantly smaller than the fabric's own thickness, solving the problem of surface unevenness caused by excessive thickness differences between high and low resistance regions due to the low conductivity of conductive nanomaterials dispersed in polymers. Through the above technical measures, the fabric structure, conductive layer, and prepreg resin form a prepreg structure with good layability and breathability, and good co-curing performance with composite materials. The interweaving characteristics of the warp and weft fiber bundles in the fabric structure, as well as the distribution and formation characteristics of conductive nanomaterials, enhance the ability of the impedance gradient prepreg to achieve the traveling wave suppression effect of the capacitance regulation mechanism. The interconnection of conductive nanomaterials forms an electrically continuous conductive network along the in-plane direction of the fabric, which has high volume conductivity, giving the impedance gradient prepreg a wide gradient resistance distribution, electrical continuity, and good thickness uniformity.
[0049] Specifically, regardless of whether the impedance gradient prepreg is gradually or continuously varied, the end with the lowest resistance is used for electrical connection with the conductive matrix of the composite material part. The lowest resistance is designed based on the resistance of the conductive matrix and the structural characteristics of the part, and is generally distributed in the range of 5~150Ω / sq (low resistance range). The thickness of the conductive layer is controlled to be less than 10µm to avoid overlapping of the conductive networks distributed on the fiber bundles, which would obscure the interlacing pores of the warp and weft fibers and compromise the capacitive-inductive balance adjustment capability. The impedance segmentation of 50~150Ω / sq in the low resistance range contributes significantly to traveling wave suppression. The conductivity of the conductive layer in the low resistance range is controlled to be ≥6.7 S / cm, ensuring that the resistance range with capacitive-inductive balance adjustment capability at least covers this low resistance range, thus improving the traveling wave suppression gain effect brought by the capacitive-inductive mechanism. For sheet resistance located in the transition range (150~200Ω / sq), the conductivity of the conductive layer is preferably ≥5 S / cm. The volume conductivity of the conductive layer is calculated by coating a conductive layer of a certain thickness on a flat glass surface and testing the thickness and sheet resistance. In addition, controlling the thickness of the conductive layer to be low and the conductivity to be high also allows the fabric to maintain good resin penetration and improves the co-curing bonding performance.
[0050] In some embodiments, a plurality of impedance segments are arranged sequentially along a first direction in a gradient distribution. The surface sheet resistance of adjacent impedance segments is different, and the surface sheet resistance of each impedance segment monotonically increases along the first direction, specifically 15Ω / sq, 70Ω / sq, 180Ω / sq, 1000Ω / sq, and 1200Ω / sq. A top view schematic diagram of the continuous fiber fabric of the traveling wave suppression impedance gradient prepreg is shown below. Figure 2 As shown, the segmented gradient in this example can be clearly observed, which enables the material to achieve good traveling wave suppression performance. A wide range of sheet resistance distributions can be achieved through the technical approach of this invention.
[0051] Specifically, the surface sheet resistance of the multiple impedance segments is distributed along the first direction according to at least one of the following: linear profile, exponential profile, cosine square profile, Taylor weighted profile, and Klopfenstein profile. A schematic diagram of the gradually changing surface sheet resistance profile design is shown below. Figure 3 As shown.
[0052] The technical approach of this invention enables the production of impedance-gradient prepregs with different cross-sectional distributions, varying numbers of impedance segments, and different widths of the impedance segments. Specifically, the number of impedance segments is 2 to 20, and the width of each impedance segment along the first direction is 5 mm to 150 mm. This is to ensure that the material achieves good traveling wave suppression performance, achieving a synergy between effectiveness and diminishing boundary effects, thus meeting the design needs of different structures.
[0053] Specifically, the continuous fiber fabric is a plain weave woven fabric, with its warp and weft densities each independently ranging from 10 to 30 strands / cm. The warp and weft fiber bundles form overlapping nodes of the conductive network at their interlacing points. The conductive nanomaterials between adjacent overlapping nodes constitute a distributed capacitance along the first direction, and the conductive fiber bundle segments extending along the first direction constitute a distributed inductance. The distributed inductance and the distributed capacitance form a capacitive-inductive distributed parameter network along the first direction, used to regulate the transmission characteristics of traveling wave current within the target frequency band. This gives the material a structure optimized for traveling wave suppression performance based on the capacitive-inductive mechanism. The warp and weft densities of 10 to 30 strands / cm each achieve optimal traveling wave suppression performance. On the other hand, if the interlacing points are too sparse, fabric deformation or fiber bundle displacement affects the continuity of the conductive network. If the interlacing point density is too high, the conductive networks formed by the conductive layers on the surfaces of the warp and weft fiber bundles easily overlap, covering the gaps between the warp and weft fiber bundles and reducing the effectiveness of the capacitive-inductive adjustment mechanism, especially in the low resistance range.
[0054] Specifically, the fibers of the continuous fiber fabric are one or more selected from quartz fiber, glass fiber, high silica fiber, basalt fiber, and aramid fiber. The areal density of the continuous fiber fabric is 30g / m² to 250g / m², and the thickness is 0.04mm to 0.25mm.
[0055] Specifically, the conductive nanomaterial is one or more of carbon nanotubes, graphene, graphite, carbon black, carbon nanofibers, and MXene; the loading amount of the conductive nanomaterial on the continuous fiber fabric is 0.01 g / m² to 12 g / m²; preferably, the loading amount of the conductive nanomaterial segmented with a sheet resistance of 50 Ω / sq or higher is 0.01 g / m² to 5 g / m². Controlling the loading amount of the conductive material maintains a good capacitance regulation mechanism in the fabric structure, while also maintaining a good interface with the structural layer.
[0056] Preferably, the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5 nm to 50 nm and a length of 5 μm to 250 μm. By controlling the diameter and length, it is easy to disperse using a lower content of dispersant, and the long tubular structure is easy to overlap to form a highly permeable conductive network. This ensures good resin permeability in the conductive layer, improving the co-cured mechanical properties, and also ensures good conductive continuity between the graded resistors. When the diameter is less than 5 nm, the interfacial properties tend to deteriorate; when the diameter is greater than 50 nm, the ability to form a conductive network decreases, resulting in uneven distribution on the fabric surface; when the tube length is less than 5 μm, the ability to form a conductive network decreases, resulting in uneven distribution on the fabric surface; when the tube length is greater than 250 μm, the conductive network overlaps under low dosage conditions, which is not conducive to forming a traveling wave suppression structure with capacitive modulation mechanism.
[0057] Specifically, the thermosetting resin is one or more of the following: medium-temperature epoxy resin, high-temperature epoxy resin, bismaleimide resin, cyanate ester resin, polyimide resin, and phenolic resin. The mass fraction of the prepreg resin in the traveling wave suppression impedance gradient prepreg is 30% to 50%.
[0058] Specifically, the continuous fiber fabric further includes multiple impedance gradient regions arranged along a second direction perpendicular to the first direction, with adjacent impedance gradient regions separated by insulating fiber zones that are not loaded with conductive nanomaterials; wherein, the surface sheet resistance distribution of the multiple impedance gradient regions is the same or different, so as to form a patterned impedance distribution within the same fabric surface.
[0059] The interwoven warp and weft structure of the fabric creates a distributed inductance in the conductive fiber bundles along the traveling wave conduction direction. This, combined with the distributed capacitance between the conductive nanomaterials, forms an inductive-capacitive distributed parameter network. The inductive reactance can be adjusted using the warp and weft weave structure to compensate for traveling wave resonance caused by a purely capacitive conductive network, achieving reflection-free absorption of traveling wave current over a wide frequency band. The equivalent circuit diagram of the fabric's inductive-capacitive distributed parameter network is shown below. Figure 4 As shown.
[0060] Specifically, the areal density of the traveling wave suppression impedance gradient prepreg is 60 g / m² to 250 g / m², the single-layer cured thickness is 0.04 mm to 0.25 mm, and the volatile content is not greater than 1.5%; preferably, the areal density is 150 g / m² to 200 g / m², the single-layer cured thickness is 0.08 mm to 0.15 mm, and the volatile content is not greater than 1.5%.
[0061] This invention also provides a method for preparing a traveling wave suppression impedance gradient prepreg, the method comprising the following steps: S1. Prepare a conductive nanomaterial dispersion; the conductive nanomaterials are uniformly dispersed in the conductive nanomaterial dispersion. S2. The conductive nanomaterial dispersion is loaded onto a continuous fiber fabric by physical deposition, and by controlling the concentration of the conductive nanomaterial dispersion and / or the number of physical depositions and / or the partitioned deposition range, the surface sheet resistance of different areas of the continuous fiber fabric is distributed according to a preset distribution, forming a conductive fabric with a gradually changing surface sheet resistance along the first in-plane direction. S3. The thermosetting resin is made into a resin film, and the resin film is combined with conductive fabric by hot melt bonding to form a prepreg, thus obtaining a traveling wave suppression impedance gradient prepreg.
[0062] Preferably, between step S2 and step S3, a stabilization pretreatment step is further included for the conductive fabric; ensuring that the change rate of the surface sheet resistance of the traveling wave suppression impedance gradient prepreg after co-curing is no greater than 30% compared to the surface sheet resistance before co-curing. And / or, in step S2, the surface sheet resistance of the conductive fabric is detected online using a four-probe method, and the concentration of the conductive nanomaterial dispersion and / or the number of physical depositions are adjusted according to the detection results.
[0063] Specifically, the stabilization pretreatment employs polymer bonding. The process conditions used in this example are as follows: the matrix resin is dissolved in acetone at a concentration of 0.5~1wt%; the conductive fabric with a gradually changing impedance is immersed in the acetone solution of the matrix resin; after drying, it is cured according to the curing requirements of the matrix resin. The purpose of the stabilization pretreatment is to make the overlapping structure of the conductive nanomaterials on the fiber bundle surface more stable, reducing the impact of resin swelling and flow on the conductive network during subsequent co-curing. After the stabilization pretreatment, the change rate of surface sheet resistance before and after co-curing can be controlled within 30%, achieving controllable resistance in engineering applications.
[0064] The four-probe online detection method can be performed at multiple locations along the first direction on the conductive fabric. The detection results are fed back to the control system, which adjusts the subsequent deposition process parameters according to the preset sheet resistance distribution target. For example, if the measured sheet resistance of a certain area is higher than the target value, the number of depositions in that area is increased or the dispersion concentration is increased; if it is lower than the target value, the number of depositions is reduced or the dispersion concentration is decreased.
[0065] Specifically, in step S1, the dispersant for dispersing the conductive nanomaterials is an aqueous dispersant, and the amount of dispersant used is not higher than 100% of the mass of the conductive nanomaterials, more preferably 15% to 70%, so that the conductive layer obtains high conductivity, and when the conductive nanomaterials are carbon nanotubes, a resin-permeable conductive network can be formed, while particularly improving the interfacial bonding of the resistance segment in the extremely low sheet resistance region (5 to 30 Ω / sq).
[0066] Specifically, the viscosity of the conductive dispersion needs to be controlled to be below 1.0 Pa·s so that the dispersion can be easily absorbed by the fiber bundles after physical deposition and form a good conductive layer that encapsulates the fiber bundles after drying.
[0067] In some embodiments, in step S1, the conductive nanomaterial dispersion can be prepared by adding the conductive nanomaterial to a dispersant solution and then dispersing it using methods such as ultrasonic dispersion or high-speed shearing. The concentration of the dispersion should be determined based on the target loading and deposition process. The concentration of the conductive nanomaterial in the dispersion is preferably 0.01wt% to 5wt%; more preferably 0.01wt% to 2wt%. The criteria for judging uniform dispersion can be: no obvious sedimentation after standing for 30 minutes, or the concentration deviation of the dispersion does not exceed 5%.
[0068] By dispersing conductive nanomaterials, controlling the deposition load, and using online resistance detection to control the deposition amount, a conductive fabric with a gradually varying sheet resistance was obtained. This fabric was then thermally melt-bonded to obtain an impedance-gradient prepreg. The amount of dispersant used was controlled to be less than 100 wt% of the conductive nanomaterials, ensuring high permeability and a good interface in the conductive layer.
[0069] In this invention, an aqueous dispersant is preferably used in the preparation process. This minimizes the impact of swelling caused by resins and other organic materials on the conductive network formed by the overlapping of carbon nanomaterials after impregnation, resulting in a more stable conductive network. Simultaneously, by controlling the amount of dispersant to be low, good permeability is maintained in both the low-resistance and high-resistance sections of the conductive fabric, ensuring good interfaces in all areas after co-curing. Consequently, the prepreg with a wide resistance range and gradual impedance variation exhibits excellent interfaces with the structural layer after co-curing.
[0070] Specifically, in step S2, the physical deposition method is one or more of dip coating, spray coating, screen printing, blade coating, and roll coating. Dip coating is suitable for large-area uniform deposition; spray coating is suitable for rapid deposition; screen printing is suitable for patterned deposition; blade coating and roll coating are suitable for continuous production. By controlling the concentration of the dispersion and / or the number of depositions, the loading of conductive nanomaterials can be adjusted, thereby adjusting the surface sheet resistance. By controlling the zoned deposition range, patterned impedance distribution can be achieved. For example, during the physical deposition process, a mask can be used to block areas where insulating fiber bands need to be formed, or the deposition range can be controlled so that conductive nanomaterials are only loaded in predetermined areas.
[0071] Specifically, in step S3, the hot-melt lamination process conditions are: temperature 50℃~100℃, pressure 0.1MPa~1MPa, time 1min~10min, or continuous roller hot-melt lamination. During the hot-melt lamination process, the resin film melts and impregnates into the pores of the conductive fabric, forming a prepreg.
[0072] This invention also provides an integrated composite material component with a wave-absorbing structure, comprising a structural prepreg stack and at least one layer of the traveling wave suppression impedance gradient prepreg provided by this invention. The traveling wave suppression impedance gradient prepreg is laid on the surface or between the layers of the structural prepreg stack, with its low-resistance section electrically connected to the conductive matrix and its high-resistance section extending towards the edge of the structure along the traveling wave propagation path. The traveling wave suppression impedance gradient prepreg and the structural prepreg stack are co-cured to form an integrated structure. A schematic diagram of the co-cured component of the traveling wave suppression impedance gradient prepreg and the structural prepreg is shown below. Figure 5 As shown.
[0073] This invention also provides an application of a traveling wave suppression impedance gradient prepreg for traveling wave suppression in the edge structure of composite materials in aircraft or spacecraft.
[0074] To better illustrate the embodiments of the present invention, the present invention will be further described in detail below through specific examples.
[0075] Example 1 Example 1 describes the preparation of a medium-temperature epoxy resistance gradient prepreg (GYIG-01 / JXT119).
[0076] The raw materials involved in this embodiment are as follows: The carrier continuous fiber fabric is QWX100P quartz fiber plain weave fabric (thickness 0.10±0.02mm, warp density 20±1 threads / cm, weft density 20±1 threads / cm, areal density 100±11g / m²).
[0077] The conductive nanomaterial is a type B multi-walled carbon nanotube (diameter 7~11nm, length 5~20μm, specific surface area 200~300m² / g).
[0078] The dispersant is sodium dodecylbenzenesulfonate, and the amount used is 50% of the mass of type B multi-walled carbon nanotubes.
[0079] The resin is JXT119 medium-temperature epoxy resin (curing temperature 130℃).
[0080] The specific steps are as follows: S1. Preparation of conductive nanomaterial dispersion: A stable, aqueous conductive dispersion was prepared using sodium dodecylbenzenesulfonate at 40% by weight of type B multi-walled carbon nanotubes.
[0081] S2. Preparation of conductive fabric: A carbon nanotube dispersion was uniformly loaded onto the surface of a quartz fiber fabric and the fiber surface layer using a physical deposition process (brush coating). The fabric surface was then dried at 120°C, allowing the carbon nanotubes to interlock and form an electrically continuous conductive network. The sheet resistance of the fabric surface was controlled by adjusting the dispersion concentration and the number of deposition cycles. Multiple impedance segments were formed on the same fabric surface along a first direction using a segmented masking method. The sheet resistance of each segment monotonically increased along the first direction. The resulting sheet resistances along the first direction were: 15 Ω / sq (width 15 mm), 70 Ω / sq (width 25 mm), 180 Ω / sq (width 35 mm), and 1000 Ω / sq (width 25 mm). The conductivity of the conductive layer was 18 S / cm. The maximum thickness difference between the segments was 32 µm. The surface density of the carbon nanotubes in each segment was measured to be 10.5 g / m³. 2 2.4g / m 2 1.3g / m 2 and 0.35g / m 2 The average load is 2.6 g / m³. 2 .
[0082] In specific control, the carbon nanotube concentrations of the dispersions used for the four resistors were 2.0wt%, 1wt%, 0.5wt%, and 0.2wt%, respectively, with viscosities all below 0.3 Pa·s. A four-probe tester (LSP probe) was used to detect the surface resistance of each region. The deviation of the sheet resistance from the target was controlled to not exceed 10wt% by the number of brush coats. The uniformity of the brush coat was controlled to ensure that the surface resistance dispersion coefficients of each region were: no more than 8% for the <100Ω / sq region, no more than 10% for the 100~1000Ω / sq region, no more than 15% for the 1000~5000Ω / sq region, and no more than 20% for the 5000~20000Ω / sq region.
[0083] S3. Preparation of prepreg: JXT119 resin was used to form a resin film using a hot melt coating machine, with the areal density controlled at 35±5g. The film was then laminated with conductive fabric using a hot melt laminating machine to obtain GYIG-01 / JXT119 medium-temperature epoxy resistance gradient prepreg.
[0084] The prepreg has a resin content of 40±4%, a surface density of 166±8 g / m², a single-layer thickness of 0.10±0.01 mm, a volatile content of ≤1.5%, and a viscosity grade of 1 or 2.
[0085] The conductive fabric obtained in this embodiment, except for the section with a sheet resistance of 15 Ω / sq, exhibits capacitance-sensitivity regulation capability in all other sections, including the low-resistance section of 70 Ω / sq which is crucial for traveling wave suppression, where the gaps between the warp and weft fiber meshes are mostly or completely uncovered by the conductive layer. Although the gaps between the warp and weft fiber meshes in the 15 Ω / sq section are completely covered by the conductive layer formed by carbon nanotubes, good permeability is maintained due to the low content of dispersant used in the carbon nanotubes, the interlocking of the carbon nanotubes, and the existence of resin penetration channels. Furthermore, it can form a good co-curing interface with the structural layer.
[0086] Application of the prepreg obtained in this embodiment: cut and lay according to the part size, match with QW280 / 1216 or QW120 / 1216 quartz fiber fabric reinforced medium temperature epoxy structural prepreg, and co-cured at 130℃; the low resistance section of the prepreg is electrically connected to the conductive substrate, and the high resistance section extends to the edge of the structure along the traveling wave propagation path.
[0087] Example 2
[0088] Example 2 describes the preparation of a high-temperature epoxy impedance gradient prepreg (GYIG-01 / JXT217).
[0089] The preparation process is the same as in Example 1, except that the resin used is JXT217 high-temperature epoxy resin (aromatic amine system, toughened with high-temperature resistant thermoplastic resin, toughened by flexible chain segments and modified with silane coupling agent), and the curing temperature is 180℃.
[0090] The obtained GYIG-01 / JXT217 impedance gradient prepreg has the following physical and chemical properties: surface density 166±8 g / m², volatile matter ≤1.5%, resin content 42±4%, single-layer thickness 0.10±0.01 mm, and glass transition temperature greater than 190℃.
[0091] GYIG-01 / JXT217 and QW280 / 1316 quartz fiber fabric reinforced high-temperature epoxy structural prepreg were co-cured using the standard autoclave curing process for the 1316 system (0.60±0.05MPa, 180±5℃, heat preservation for 2~3h).
[0092] The average adhesion strength, measured by the pull-out method according to GB / T5210, was 25.32 MPa. The failure location was in the adhesive layer of the loading block, indicating good compatibility and reliable adhesion between the two materials. The mechanical properties (room temperature dry state) of the composite material after co-curing met the following requirements: tensile strength ≥ 500 MPa, tensile modulus ≥ 16 GPa, compressive strength ≥ 400 MPa, compressive modulus ≥ 16 GPa, flexural strength ≥ 500 MPa, flexural modulus ≥ 15 GPa, interlaminar shear strength ≥ 60 MPa, and adhesion strength ≥ 15 MPa. After water resistance, RP-3 fuel oil resistance, No. 15 hydraulic oil resistance, 4109 lubricating oil resistance, damp heat resistance, and salt spray resistance tests, the pencil hardness reached 9H, and the adhesion strength was ≥ 15 MPa.
[0093] After obtaining the conductive fabric in step S2 of this embodiment, the conductive fabric is pre-treated for stabilization and then composited with the resin film and cured. The change rate of surface sheet resistance before and after curing can be controlled within 30% (typical value 5%~11%), and the change rate has good batch reproducibility. The resistance after co-curing can be precisely controlled by preset fabric target resistance.
[0094] Example 3
[0095] Example 3 describes the preparation of a bismaleimide resin impedance gradient prepreg (GYIG-01 / JXT320).
[0096] The preparation process is the same as in Example 1, except that: JXT320 bismaleimide resin is used, which is matched with QW280 / 5429 or QW120 / 5429 quartz fiber fabric reinforced bismaleimide prepreg, and co-cured according to the bismaleimide resin system curing regime, which is suitable for structural parts with higher temperature resistance.
[0097] Example 4
[0098] Example 4 describes the preparation of a cyanate ester impedance gradient prepreg.
[0099] The preparation process is the same as in Example 1, except that cyanate ester resin is used. Cyanate ester resin has the characteristics of low dielectric constant and low loss tangent. The resulting impedance gradient prepreg has better dielectric compatibility with adjacent transparent layers in co-curing structures that require high wave transmission / dielectric properties. It is co-cured according to the cyanate ester resin system curing regime.
[0100] Example 5
[0101] Example 5 describes the preparation of a polyimide impedance gradient prepreg.
[0102] The preparation process is the same as in Example 1, except that the resin used is polyimide resin, which is suitable for high-temperature structural parts that can withstand long-term temperatures above 250°C, and is co-cured according to the curing regime of polyimide resin system.
[0103] Example 6
[0104] Example 6 describes the preparation of patterned impedance distribution and broadband traveling wave suppression.
[0105] Based on any of Examples 1 to 5, multiple impedance gradient regions arranged along the second direction are formed in the same fabric surface by partition deposition (partition masking), with the intervals separated by insulating fiber zones without carbon nanotubes, to achieve patterned impedance customization; the surface sheet resistance of each impedance gradient region along the first direction (traveling wave propagation direction) increases monotonically from the low resistance end to the high resistance end. For example, a 50mm~300mm wide impedance gradient fabric consists of 3~5 impedance segments: taking a 100mm wide fabric as an example, zone 1 is 15mm-15Ω / sq, zone 2 is 25mm-70Ω / sq, zone 3 is 35mm-180Ω / sq, and zone 4 is 25mm-1000Ω / sq; taking a 300mm wide fabric as an example, zone 1 is 30mm-15Ω / sq, zone 2 is 60mm-60Ω / sq, zone 3 is 60mm-150Ω / sq, zone 4 is 70mm-350Ω / sq, and zone 5 is 80mm-1200Ω / sq.
[0106] Example 7
[0107] Example 7 describes the preparation of a high-temperature epoxy resistance gradient prepreg (GYIG-EW01 / JXT217). The raw materials involved in this embodiment are as follows: The carrier continuous fiber fabric is EW50 glass fiber plain weave fabric (thickness 0.05±0.02mm, warp density 12.5±1 threads / cm, weft density 12.5±1 threads / cm, areal density 48±4g / m²).
[0108] The resin is JXT217 high-temperature epoxy resin (curing temperature 180℃).
[0109] The specific preparation steps are as follows: S1. Prepare two dispersions of conductive nanomaterials: a) A co-dispersion of type B multi-walled carbon nanotubes (diameter 7~11nm, length 5~20μm, specific surface area 200~300m² / g) and single-walled carbon nanotubes (diameter 0.7~1.7nm, length 20~50μm), with a mass ratio of the two conductive agents of 1:2, and the dispersant being carboxymethyl cellulose, which accounts for 75% of the total mass of the conductive agents, was prepared into a stable aqueous conductive dispersion. b) Type B multi-walled carbon nanotubes, with sodium dodecylbenzenesulfonate as the dispersant, are used in an amount of 50% of the mass of the type B multi-walled carbon nanotubes to form a stable and dispersed aqueous conductive dispersion.
[0110] S2. Preparation of conductive fabric: A physical deposition process (spraying) is used to uniformly load a dispersion of conductive material onto the surface of EW50 fabric and the fiber surface layer. The dispersion on the fabric surface is then dried at 120°C. After drying, carbon nanotubes interlock to form an electrically continuous conductive network. The sheet resistance of the fabric surface is controlled by adjusting the dispersion concentration and the number of depositions. Multiple impedance segments are formed on the same fabric surface along a first direction using a segmented masking method. The sheet resistance of each segment increases monotonically along the first direction. The resulting sheet resistances of each segment along the first direction are as follows: 1 The carbon nanotube segments were 5Ω / sq (10mm width), 150Ω / sq (25mm width), and 1200Ω / sq (15mm width). The conductivity of the conductive layer in the 15Ω / sq region was 127S / cm, while the conductivity in the 150Ω / sq and 1200Ω / sq regions was 17S / cm. The maximum thickness difference between the segments was 5µm, demonstrating extremely high thickness uniformity. Most or all of the warp and weft fiber gaps in each resistive segment were preserved, maintaining capacitance regulation capability, good resin permeability, and interfacial adhesion. The areal density of the carbon nanotubes in each segment was measured to be 1.8 g / m³. 2 1.5g / m 2 and 0.31g / m 2 The average load is 1.20 g / m³. 2 .
[0111] In specific control, the concentration of dispersion a used in the 15Ω / sq segment was 0.1wt% (viscosity 0.63 Pa·s), while the carbon nanotube concentrations of dispersion b used in the other two sheet resistance segments were 0.5wt% and 0.2wt%, respectively, with viscosities both below 0.1 Pa·s. A four-probe tester (LSP probe) was used to detect the surface resistance of each zone. The deviation between the sheet resistance and the target was controlled to not exceed 10wt% by the number of brush coats. The uniformity of the brush coat was controlled to ensure that the surface resistance dispersion coefficients of each zone were: no more than 8% for the <100Ω / sq region, no more than 10% for the 100~1000Ω / sq region, no more than 15% for the 1000~5000Ω / sq region, and no more than 20% for the 5000~20000Ω / sq region.
[0112] S3. Preparation of prepreg: JXT217 resin was used to form a resin film using a hot melt coating machine, with the areal density controlled at 32±3g. Then, one layer of the film was combined with a stabilized and pretreated conductive fabric using a hot melt laminating machine to obtain GYIG-EW01 / JXT217 high-temperature epoxy resistance gradient prepreg.
[0113] The prepreg has a resin content of 40±4%, a surface density of 80±8 g / m², a single-layer thickness of 0.05±0.01 mm, and a volatile content of 0.24%.
[0114] Application of the prepreg obtained in this embodiment: cut and laid according to the part size, matched with QW280 / 1316 quartz fiber fabric reinforced high-temperature epoxy structural prepreg, and co-cured at 180℃; the low-resistance end of the prepreg is electrically connected to the conductive substrate, and the high-resistance end extends to the edge of the structure along the traveling wave propagation path.
[0115] Example 8
[0116] Example 1 describes the preparation of a high-temperature epoxy impedance gradient prepreg (GYIG-E02 / JXT217).
[0117] The raw materials involved in this embodiment are as follows: The carrier continuous fiber fabric is a high-silica glass fiber plain weave fabric (thickness 0.15±0.02mm, warp density 12.5±1 threads / cm, weft density 12.5±1 threads / cm, areal density 152±15g / m²).
[0118] The conductive nanomaterial is a multi-walled carbon nanotube (diameter 5~10nm, length 50~150μm, specific surface area 200~300m² / g).
[0119] Sodium dodecylbenzenesulfonate was used as the dispersant, and its dosage was 20% of the mass of type B multi-walled carbon nanotubes.
[0120] A stable and dispersed aqueous conductive dispersion was prepared; the resin was JXT217 high-temperature epoxy resin (curing temperature 180℃).
[0121] The specific preparation steps are as follows: S1. Preparation of conductive nanomaterial dispersion: A stable, aqueous conductive dispersion was prepared using sodium dodecylbenzenesulfonate at 20% by weight of multi-walled carbon nanotubes.
[0122] S2. Preparation of Conductive Fabric: A carbon nanotube dispersion is uniformly loaded onto the surface of a high-silica glass fiber fabric and the fiber surface layer using a physical deposition process (spraying). The dispersion on the fabric surface is then dried at 120°C. After drying, the carbon nanotubes overlap to form an electrically continuous conductive network. The sheet resistance of the fabric surface is controlled by adjusting the dispersion concentration and the number of depositions. Multiple impedance segments are formed on the same fabric surface in a segmented shielding manner, arranged sequentially along a first direction. The sheet resistance of each segment increases monotonically along the first direction. The resistances along the first direction are 15Ω / sq (30mm width), 60Ω / sq (60mm width), 150Ω / sq (60mm width), 350Ω / sq (70mm width), and 1200Ω / sq (80mm width). The conductivity of the conductive layer is 20~25S / cm, and the maximum thickness difference between each segment is 29µm. The gaps between the warp and weft fibers in the segments with a sheet resistance of 60Ω / sq and above are partially or completely preserved, maintaining capacitance regulation capability, good resin permeability, and interfacial adhesion. The areal density of the carbon nanotubes in each segment was measured to be 9.3g / m³. 2 2.3g / m 2 1.33g / m 2 0.64g / m 2 and 0.25g / m 2 The average load is 1.87 g / m³. 2 .
[0123] In specific control, the carbon nanotube concentrations of the dispersions used for the four resistors were 1.5wt%, 1.0wt%, 0.5wt%, and 0.2wt%, respectively (all with viscosities below 0.5 Pa·s). A four-probe tester (LSP probe) was used to detect the surface resistance of each zone. The deviation of the sheet resistance from the target was controlled to not exceed 10wt% by the number of brush coats. The uniformity of the spraying was controlled to ensure that the surface resistance dispersion coefficients of each zone were: no more than 8% for the <100Ω / sq region, no more than 10% for the 100~1000Ω / sq region, and no more than 15% for the 1000~5000Ω / sq region.
[0124] S3. Preparation of prepreg: JXT217 resin was used to form a resin film using a hot melt coating machine, with the areal density controlled at 40±4g. Then, two films were laminated with a stabilized and pretreated conductive fabric using a hot melt laminating machine to obtain GYIG-E02 / JXT217 high-temperature epoxy impedance gradient prepreg.
[0125] The prepreg has a resin content of 38±4%, a surface density of 230±10 g / m², a single-layer thickness of 0.15±0.01 mm, and a volatile content of 0.15%.
[0126] Application of the prepreg obtained in this embodiment: cut and laid according to the part size, matched with QW280 / 1316 quartz fiber fabric reinforced high-temperature epoxy structural prepreg, and co-cured at 180℃; the low-resistivity section of the prepreg is electrically connected to the conductive substrate, and the high-resistivity section extends to the edge of the structure along the traveling wave propagation path.
[0127] Traveling wave suppression effect: The traveling wave suppression sample (with the low-resistivity section overlapping the conductive substrate of the metal plate and the traveling wave incident from the high-resistivity section) made using the impedance-gradient fabric of Example 2 of this invention was tested for its RCS traveling wave peak in the range of 0.44 GHz to 9.41 GHz. Compared with a bare metal plate, the following results were observed: at 1.3 GHz, the traveling wave peak decreased from -12.00 dBsm to -30.30 dBsm (suppression coefficient 30.4 dBsm·m⁻¹); at 3 GHz, it decreased from -13.10 dBsm to -49.70 dBsm (suppression coefficient 61.0 dBsm·m⁻¹); and at 5.6 GHz, the suppression was 17.5 dB (reduced to -21 dBsm, suppression coefficient 29.17). dBsm·m⁻¹), with a suppression of 16.6 dB at 9.41 GHz (reduced to -31 dBsm, suppression coefficient 27.67 dBsm·m⁻¹), and a traveling wave suppression coefficient as high as 61 dBsm·m⁻¹, see [reference needed]. Figure 6 .
[0128] The traveling wave suppression sample (with the low-resistivity section overlapping the conductive substrate of the metal plate and the traveling wave incident from the high-resistivity section) made using the impedance gradient fabric of Example 7 of this invention was tested for RCS traveling wave peak in the range of 0.44 GHz to 9.41 GHz. Compared with the bare metal plate, the traveling wave peak at 1.3 GHz was reduced to -21.00 dBsm (suppression of 16.36 dB), at 3 GHz to -26.20 dBsm (suppression of 23.82 dB), at 5.6 GHz to -24.80 dBsm (suppression of 19.64 dB), and at 9.41 GHz to -31.90 dBsm (suppression of 31.82 dB). The highest traveling wave suppression coefficient was 31.82 dBsm·m⁻¹.
[0129] The traveling wave suppression sample (with the low-resistivity section overlapping the conductive substrate of the metal plate and the traveling wave incident from the high-resistivity section) made using the impedance gradient fabric of Example 8 of this invention was tested for RCS traveling wave peak in the range of 0.44GHz to 9.41GHz. Compared with the bare metal plate, the traveling wave peak at 1.3GHz dropped to -32.50dBsm (suppression of 25.63dB), at 3GHz it dropped to -32.90dBsm (suppression of 24.75dB), at 5.6GHz it dropped to -33.00dBsm (suppression of 23.75dB), and at 9.41GHz it dropped to -32.70dBsm (suppression of 22.88dB). The traveling wave suppression coefficient at the above frequencies was higher than 22dBsm·m⁻¹.
[0130] Comparative Example 1 This comparative example prepares a traditional PET film carrier impedance gradient film. The conductive coating (20 parts of type B multi-walled carbon nanotubes, 10 parts of PEK-C, 50 parts of JXT217 high-temperature epoxy resin, and 120 parts of N,N-dimethylacetamide, mixed and dissolved, and then ball-milled for 2 hours to disperse evenly into a paste) was applied to the surface of a PET film (thickness 0.05 mm), dried to form a film with a conductivity of 3.27 S / cm. The resistance and width of the coating were the same as in Example 1.
[0131] The traditional impedance gradient film, which uses PET film as a carrier and has a screen-printed resistive layer on its surface, achieves a coating thickness of 200 μm for the 15 Ω / sq sheet resistance segment, while the theoretical thickness for the 1000 Ω / sq sheet resistance segment is only 3 μm, making coating difficult and resulting in a significant thickness difference. In practice, it can only be adhered to the structural surface using pressure-sensitive adhesive. Firstly, PET has low surface energy, and the interface is only connected by the adhesive layer, resulting in an adhesion strength of 6.94 MPa, far lower than the co-cured interface (25.32 MPa) in Example 2, making it prone to detachment under vibration and temperature cycling. Secondly, PET film is dense and impermeable, easily forming diffuse pores at the interface when laminated and cured with prepreg. Thirdly, PET film is not deformable within its surface, making it impossible to conformally fit hyperbolic surfaces.
[0132] The conventional PET film carrier impedance gradient film with the same sheet resistance section as in Examples 1 and 2 was encapsulated with tape to prepare a traveling wave suppression sample (the low resistance section overlapped with the conductive substrate of the metal plate, and the traveling wave was incident from the high resistance section side). The RCS traveling wave peak was tested in the range of 0.44 GHz to 9.41 GHz. Compared with the bare metal plate, the traveling wave peak dropped to -27.10 dBsm at 1.3 GHz, to -44.90 dBsm at 3 GHz, to -27.90 dBsm at 5.6 GHz, and to -26.20 dBsm at 9.41 GHz. It was generally 3 to 5 dBsm worse than Example 2. The highest traveling wave suppression coefficient was 53 dBsm·m⁻¹, which was about 8 dBsm·m⁻¹ worse than Example 2.
[0133] Comparative Example 2 This comparative example prepares a carbonyl iron-type traveling wave suppression coating.
[0134] Traditional traveling wave suppression coatings, which involve coating carbonyl iron-type absorbers onto metal surfaces, are difficult to suppress low-frequency traveling waves, have poor high-temperature thermal stability, high density, and are prone to peeling off, making it impossible to integrate them with the structure.
[0135] Comparative Example 3 This comparative example involves directly coating the fabric with a conductive coating. The conductive coating (with the same composition as Comparative Example 1) was applied to the surface of the quartz fiber fabric and dried to form a film. The sheet resistance and width of the resulting resistive segments were the same as in Examples 1 and 2.
[0136] The above method has the following problems: (1) Carbon nanotubes exist in the coating in the form of dispersion in the resin rather than overlapping each other. The conductive network is filled by the resin, resulting in low conductivity of the conductive layer. The thickness of the low resistance section and the sheet resistance section of 15Ω / sq reaches 262μm, while the thickness of the sheet resistance section of 1200Ω / sq is only 110μm, resulting in step protrusion after co-curing and laying. In addition, due to the low conductivity of the conductive layer, the coating is thick. The poor fluidity of the coating does not spontaneously adsorb and wrap the fiber bundle. The gaps between the warp and weft yarns in the sheet resistance sections of 15Ω / sq, 70Ω / sq, and 180Ω / sq are completely covered by the coating formed by the conductive coating. Most of the gaps between the warp and weft yarns in the 1000Ω / sq resistance section are covered by the coating formed by the conductive coating, which makes it impossible to play the traveling wave suppression regulation function of the capacitance regulation mechanism. At the same time, it hinders the permeability of the resin and brings about problems similar to those in Comparative Example 1.
[0137] Comparative Example 4 This comparative example uses the same method as Example 2, except that the amount of dispersant used in the conductive dispersion is increased to 125 wt% of carbon nanotubes.
[0138] The results showed that the adhesion strength of the low resistance section (15Ω / sq sheet resistance section) decreased to 13.2MPa. The large amount of residual dispersant between the conductive networks hindered the penetration of the resin and degraded the interface. Furthermore, the gaps between the warp and weft yarns of the fabric in the 15Ω / sq sheet resistance section were completely filled by the conductive network, and the 70Ω / sq sheet resistance section was also almost completely filled, resulting in a decrease in capacitance regulation capability.
[0139] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0140] For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A traveling wave suppression impedance-gradient prepreg, characterized in that, The traveling wave suppression impedance gradient prepreg comprises a continuous fiber fabric, a conductive layer, and a prepreg resin; The continuous fiber fabric includes warp fiber bundles extending along the warp direction and weft fiber bundles extending along the weft direction, wherein the warp fiber bundles and the weft fiber bundles interweave to form a fabric structure. The conductive layer is a conductive nanomaterial loaded on the surface of the warp fiber bundle and / or the weft fiber bundle, and the conductive nanomaterials overlap each other to form an electrically continuous conductive network along the in-plane direction of the continuous fiber fabric. The prepreg resin is impregnated in a continuous fiber fabric and a conductive layer to form a prepreg shape that can be laid out. The surface sheet resistance of the conductive layer is gradually distributed along a first direction within the surface of the continuous fiber fabric, and the first direction is the direction of conduction of the traveling wave current during use; the prepreg resin is a thermosetting resin that can be co-cured with the structural prepreg.
2. The traveling wave suppression impedance gradient prepreg according to claim 1, characterized in that, The range of the surface sheet resistance is 5Ω / sq to 20000Ω / sq; The gradual distribution of the surface sheet resistance is selected from one or a combination of the following: a. The gradient distribution is arranged in sequence along the first direction, with multiple impedance segments having different surface sheet resistances of adjacent impedance segments, and the surface sheet resistance of each impedance segment changes monotonically along the first direction. b. The surface sheet resistance changes continuously and gradually along the first direction.
3. The traveling wave suppression impedance gradient prepreg according to claim 2, characterized in that, The gradient distribution includes a low-resistance section, a transition section, and a high-resistance section, wherein the lowest end of the surface sheet resistance of the low-resistance section is used for electrical connection with the conductive substrate. The surface sheet resistance of the low-resistance section is 5Ω / sq~150Ω / sq, the surface sheet resistance of the transition section is 150Ω / sq~200Ω / sq, and the surface sheet resistance of the high-resistance section is 200Ω / sq~20000Ω / sq.
4. The traveling wave suppression impedance gradient prepreg according to claim 2, characterized in that, The surface sheet resistance of multiple impedance segments is distributed along the first direction according to at least one of the following: linear profile, exponential profile, cosine square profile, Taylor weighted profile, and Klopp-Fenstein profile. The number of the plurality of impedance segments is 2 to 20, and the width of each impedance segment along the first direction is 5 mm to 150 mm.
5. The traveling wave suppression impedance gradient prepreg according to claim 1, characterized in that, The continuous fiber fabric is a plain weave woven fabric, with its warp density and weft density each being 10 threads / cm to 30 threads / cm independently; The fibers of the continuous fiber fabric are one or more of the following: quartz fiber, glass fiber, high silica fiber, basalt fiber, and aramid fiber. The conductive nanomaterial is one or more of carbon nanotubes, graphene, graphite, carbon black, carbon nanofibers, and MXene. The thermosetting resin is one or more of the following: medium-temperature epoxy resin, high-temperature epoxy resin, bismaleimide resin, cyanate ester resin, polyimide resin, and phenolic resin.
6. The traveling wave suppression impedance gradient prepreg according to claim 5, characterized in that, The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5 nm to 50 nm and a length of 5 μm to 250 μm.
7. The traveling wave suppression impedance gradient prepreg according to claim 1, characterized in that, The loading amount of the conductive nanomaterial on the continuous fiber fabric is 0.01 g / m² to 12 g / m². The areal density of the continuous fiber fabric is 30g / m² to 250g / m², and the thickness is 0.04mm to 0.25mm. The preimpregnated resin has a mass fraction of 30% to 50% in the traveling wave suppression impedance gradient preimpregnated material; The areal density of the traveling wave suppression impedance gradient prepreg is 60g / m² to 250g / m², the single-layer cured thickness is 0.04mm to 0.25mm, and the volatile content is not greater than 1.5%.
8. The traveling wave suppression impedance gradient prepreg according to claim 1, characterized in that, The continuous fiber fabric also includes multiple impedance gradient regions arranged along a second direction perpendicular to the first direction, and adjacent impedance gradient regions are separated by insulating fiber zones that are not loaded with conductive nanomaterials. Among them, the surface sheet resistance distribution of multiple impedance gradient regions is the same or different, so as to form a patterned impedance distribution within the same fabric surface.
9. A method for preparing a traveling wave suppression impedance-gradient prepreg according to any one of claims 1-8, characterized in that, The method includes the following steps: S1. Prepare a dispersion of conductive nanomaterials; S2. The conductive nanomaterial dispersion is loaded onto a continuous fiber fabric by physical deposition, and by controlling the concentration of the conductive nanomaterial dispersion and / or the number of physical depositions and / or the partitioned deposition range, the surface sheet resistance of different areas of the continuous fiber fabric is distributed according to a preset distribution, forming a conductive fabric with a gradually changing surface sheet resistance along the first in-plane direction. S3. The thermosetting resin is made into a resin film, and the resin film is combined with conductive fabric by hot melt bonding to form a prepreg, thus obtaining a traveling wave suppression impedance gradient prepreg.
10. The method for preparing a traveling wave suppression impedance-gradient prepreg according to claim 9, characterized in that, Between step S2 and step S3, there is also a step of stabilizing the conductive fabric.
11. A composite material component integrating microwave absorbing structure and function, characterized in that, The structure includes a structural prepreg stack and at least one layer of traveling wave suppression impedance gradient prepreg as described in any one of claims 1-8. The traveling wave suppression impedance gradient prepreg is laid on the surface or between the layers of the structural prepreg stack, wherein the low-resistance section has the lowest surface sheet resistance and is electrically connected to the conductive substrate, and the high-resistance section extends along the traveling wave propagation path to the edge of the structure. The traveling wave suppression impedance gradient prepreg and the structural prepreg stack are co-cured to form an integral structure.
12. An application of a traveling wave suppression impedance-gradient prepreg according to any one of claims 1-8, characterized in that, Traveling wave suppression applied to the edge structures of composite materials in aircraft or spacecraft.
Citation Information
Patent Citations
Edge gradual impedance loading thin film and edge gradual impedance loading structure
CN102570047B
A Discontinuous Impedance Gradient Structure Absorbing Composite Material
CN106671514B
An integrated impedance gradient flexible absorbing material and its preparation method
CN112538761B
